1995
DOI: 10.1530/eje.0.1320722
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and selective cure of Cushing's disease during pregnancy by transsphenoidal surgery

Abstract: The diagnosis of Cushing's Disease during pregnancy is complex because the biochemical features are obscured by changes in the normal hypothalamo-pituitary-adrenal axis that occur during gestation. To date, treatment has not been successful and there is a high incidence of maternal and fetal complications. We report the case of a 24-year-old woman with Cushing's disease who presented during her 16th week of pregnancy. Diagnosis was confirmed by the finding of elevated serum and urinary free cortisol levels wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 8 publications
(11 reference statements)
0
33
0
Order By: Relevance
“…One of the most helpful means to distinguish Cushing's syndrome from hypercortisolism of normal pregnancy is to uncover loss of normal circadian variation in increased cortisol levels [15]. Furthermore, Ross et al reported the significance of exaggerated ACTH response to CRH in a pregnant woman with Cushing's disease [16]. Unfortunately we could not assess the endocrine condition of our patient before delivery; however, the combination of CRH test and daily profile of circulating ACTH and cortisol would have been a safe and beneficial method for the early recognition of Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most helpful means to distinguish Cushing's syndrome from hypercortisolism of normal pregnancy is to uncover loss of normal circadian variation in increased cortisol levels [15]. Furthermore, Ross et al reported the significance of exaggerated ACTH response to CRH in a pregnant woman with Cushing's disease [16]. Unfortunately we could not assess the endocrine condition of our patient before delivery; however, the combination of CRH test and daily profile of circulating ACTH and cortisol would have been a safe and beneficial method for the early recognition of Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although the experience of other drugs, such as aminoglutethimide [18], mitotane [10,19], bromocriptine [9] and cyproheptadine [20][21][22][23][24], was also reported, aminoglutethimide and mitotane should be avoided as much as possible because of their potential toxicity to fetus. Transsphenoidal surgery of pituitary ACTH-secreting adenoma was carried out successfully in five patients during pregnancy [11,16,[25][26][27]. Even radiation therapy was performed in a case of Cushing's disease during pregnancy [6].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, urinary free cortisol secretion increases in normal pregnancy and modestly elevated levels (≈100-300 µg/24 h) are compatible with pregnancy per se [17,21]. Conversely, urinary free cortisol levels in pregnant patients with Cushing's syndrome are reportedly extremely high [22,23] and most often do not overlap with levels observed in normal pregnant women. Resistance to cortisol feedback in pregnancy calls for higher cortisol cut-off values after low dose dexamethasone (1 mg overnight).…”
Section: Diagnostic Evaluation For Cushing's Disease During Gestationmentioning
confidence: 96%
“…Most patients with Cushing's disease diagnosed during pregnancy present ACTH levels in the upper half of the normal range or even higher [23,25,26]. Conversely, out of nearly 30 reported cases with adrenal Cushing's syndrome diagnosed during pregnancy, the majority displayed undetectable or subnormal ACTH levels, 10 and 15 patients, respectively, while ACTH levels were in the normal range only in 4 patients.…”
Section: Diagnostic Evaluation For Cushing's Disease During Gestationmentioning
confidence: 98%
See 1 more Smart Citation